2023
DOI: 10.3390/atmos14101579
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Multi-Station Atmospheric Electric Field Anomalies before the Yangbi Ms 6.4 Earthquake on 21 May 2021

Lei Nie,
Xuemin Zhang

Abstract: This study reports the atmospheric electric field (AEF) anomalies associated with seismic-geological activity recorded by the monitoring network in the Sichuan–Yunnan region of China during the 15–30 days prior to the Yangbi earthquake in Yunnan Province, China, on 21 May 2021. Based on the real-time AEF data from continuous observation, this study summarized the characteristics of the anomalous interference of different meteorological factors on the AEF, compared the simultaneous meteorological data of the AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The previous workers [e.g., [30] [31] [32]] observed the anomalies in atmospheric electric field only on the order of a few hundred V/m. But, a recent extensive paper has been published based on the multi-station observation in China by Nie and Zhang (2023) [33], who have tried to extract the seismogenic atmospheric electric field changes associated with a particular EQ by eliminating climate-related perturbations. They have found that the anomalies appeared 15 -30 days before the EQ, electric field anomalies followed a consistent trend (with the electric field initially decreasing following sunny days before rising again, showcasing a decrease of 1 -3 kV/m, one order higher than the previous results), and the duration of anomaly fluctuations is concentrated to a range of 30 -60 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…The previous workers [e.g., [30] [31] [32]] observed the anomalies in atmospheric electric field only on the order of a few hundred V/m. But, a recent extensive paper has been published based on the multi-station observation in China by Nie and Zhang (2023) [33], who have tried to extract the seismogenic atmospheric electric field changes associated with a particular EQ by eliminating climate-related perturbations. They have found that the anomalies appeared 15 -30 days before the EQ, electric field anomalies followed a consistent trend (with the electric field initially decreasing following sunny days before rising again, showcasing a decrease of 1 -3 kV/m, one order higher than the previous results), and the duration of anomaly fluctuations is concentrated to a range of 30 -60 minutes.…”
Section: Introductionmentioning
confidence: 99%